2019
DOI: 10.1371/journal.pone.0214480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought-stress on seed germination and growth physiology of quinclorac-resistant Echinochloa crusgalli

Abstract: Echinochloa crusgalli (L.) Beauv. (barnyard grass) is considered a noxious weed worldwide, and is the most pernicious weed decreasing rice yields in China. Recently, E . crusgalli has evolved quinclorac resistance, making it among the most serious herbicide resistant weeds in China. The present study explored differences in germination and growth between quinclorac-resistant and -susceptible E . crusgalli col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
3
21
0
4
Order By: Relevance
“…Several studies have assessed weed seed germination using PEG 6000 to impose drought stress [14, 16] including in Asteraceae species [11, 17]. It has been suggested that PEG reduces the water potential of osmotic solutions and thus can be used for drought stress studies [13].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have assessed weed seed germination using PEG 6000 to impose drought stress [14, 16] including in Asteraceae species [11, 17]. It has been suggested that PEG reduces the water potential of osmotic solutions and thus can be used for drought stress studies [13].…”
Section: Resultsmentioning
confidence: 99%
“…Drought stress inhibits seed germination and plant growth [32,33]. Exogenous melatonin plays an important role in improving seed germinations under different abiotic stress conditions such as water deficit [34], high temperature [35], cold [13], and salt stress [36].…”
Section: Discussionmentioning
confidence: 99%
“…Drought is a predominant abiotic stress, which significantly affects plant response to herbicides, primarily reducing efficacy [44]. Reduced herbicide efficacy has been documented when weeds are under drought stress [45][46][47]. Drought causes multiple changes in the molecular, biochemical, and physiological state of the plant, with various consequences including reduced absorption and translocation of herbicide, preventing the active ingredient from reaching the target site, thus contributing to survival [45][46][47].…”
Section: Introductionmentioning
confidence: 99%